Engaging community groups to enhance healthcare access for persons with disabilities in rural Uganda: A qualitative exploration. - Andrew Sentoogo Ssemata; Tracey Smythe; Slivesteri Sande; Abdmagidu Menya; Shaffa Hameed; Peter Waiswa; Femke Bannink Mbazzi; Hannah Kuper (PLOS Global Public Health)
Community participation is a promising strategy for addressing local health needs through identification of context-specific challenges and developing sustainable solutions. However, its feasibility for persons with disabilities, who are often marginalized and excluded from participation, remains uncertain. Our study examines barriers and facilitators to community group participation in improving healthcare access for persons with disabilities in Uganda. Semi-structured interviews with 27 purposively selected persons with disabilities in Luuka district, Eastern Uganda were undertaken between September and November 2022. Questions were asked about participation in existing groups and interest in joining community groups for persons with disabilities to improve healthcare access. All interviews were recorded and transcribed and analysed with a thematic approach. Our study uncovered a notable lack of active engagement among persons with disabilities in existing community groups. Participants expressed a strong desire to belong to disability-focused groups, primarily driven by the desire for unified advocacy. Facilitators for group formation included the opportunity for collaborative problem-solving, unified advocacy, and the chance to share lived experiences. Conversely, barriers to participation encompassed issues such as low self-esteem, financial constraints preventing monetary contributions, and the lack of reasonable accommodations, such as inaccessible meeting venues. Recommendations for group formation included community-wide sensitisation, stakeholder engagement, integration of health-livelihood initiatives, linkage to services, and managing group dynamics to ensure inclusiveness, a manageable group size, and realistic monetary contributions. Persons with disabilities are eager to participate in community groups and recognize the importance of strengthening community-based healthcare initiatives. Addressing barriers to group formation can unlock the potential of these groups to support persons with disabilities effectively. These findings offer valuable insights for developing community-based interventions to enhance healthcare access for persons with disabilities. Further research is essential to fully grasp the key mechanisms and dynamics within these groups to ensure their long-term sustainability.